Risk factors of cardiovascular disease nowadays - R. A. Fedorchenko; V. L. Mykhaylenko (Kazimierz Wielki University, 2020)
The article analyzes the incidence of the population of Ukraine and the Zaporozhye region by class of diseases of the cardiovascular system, studied the structure and causes of mortality from CVD, cardiovascular disease risk factors. It is established that the number of adults who have diseases of the cardiovascular system in Ukraine has reached 26,4 million (58% of the population), more than 400 thousand. people die every year, about 14-15 people out of every 10 thousand adults become disabled. It was found that urban residents of the Zaporozhye region more often than rural (1,3 times, p <0,05) have CVD, and in Melitopol, Zaporozhye, Bilmatsky, Orekhovsky, Veselovsky and Berdyansky districts the incidence rate exceeds the national rate. In V-Belozersky, Zaporozhye, Mikhailovsky, Rozovsky and N-Nikolaevsky areas high levels of morbidity on a hypertensive disease with excess of republican level within 1,5-3,5 times (р<0,05) are registered. The prevalence of coronary heart disease was in line with the national trend, but in 19 districts of the Zaporizhia region the prevalence of strokes was 2,5 times (р<0,05) higher than the Ukrainian average; and in 11 - the prevalence of myocardial infarction exceeded the national level. In the structure of causes of death from CVD, the share of coronary heart disease was 68,9%; cerebrovascular disease - 19,7%, strokes - 8.3%; myocardial infarction (all forms) - 2,5%. Adverse demographic situation inUkraine, including Zaporozhye region is largely due to cardiovascular diseases, which significantly affect the main indicators of public health. A stable increase in the general mortality rate and a decrease in life expectancy are of serious concern and indicate the insufficient effectiveness of preventive measures. First of all, preventive measures should be planned in those areas of the Zaporizhzhya region, where the incidence and mortality rates exceed the average regional and republican indicators. These are such cities of Zaporozhye, Melitopol, Energodar and such regions Rozovsky, Tokmack, Zaporizhia and B-Belozersky areas.